2023
DOI: 10.1111/1462-2920.16329
|View full text |Cite
|
Sign up to set email alerts
|

Underexplored viral auxiliary metabolic genes in soil: Diversity and eco‐evolutionary significance

Abstract: Bacterial viruses are the most abundant biological entities in soil ecosystems. Owing to the advent of metagenomics and viromics approaches, an ever‐increasing diversity of virus‐encoded auxiliary metabolic genes (AMGs) have been identified in soils, including those involved in the transformation of carbon, phosphorus, and sulfur, degradation of organic pollutants, and antibiotic resistance, among other processes. These viral AMGs can alter soil biogeochemical processes and metabolic activities by interfering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In summary, 8 out of 25 phages (32%) have potential AMGs present in their genome. It should be noted that there is currently a lack of a database and pipeline to annotate and identify AMGs in a robust and reliable manner [28]. Future research could aim to validate the function of these particular genes in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, 8 out of 25 phages (32%) have potential AMGs present in their genome. It should be noted that there is currently a lack of a database and pipeline to annotate and identify AMGs in a robust and reliable manner [28]. Future research could aim to validate the function of these particular genes in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…When focusing on lifestyle-specific viruses, AMGs encoded by both lytic and temperate viruses are habitatdependent and host-specific [45]. AMGs are host-specific to some extent, and studies have shown that viral AMGs can be acquired and maintained from their hosts [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to facilitating horizontal gene transfer, temperate phages are also capable of altering host metabolism through the expression of AMGs (Yu et al 2015 , Sun et al 2023a ) (Fig. 1D ).…”
Section: Introductionmentioning
confidence: 99%
“…In cyanophages, AMGs have been associated with functions such as photosynthesis, nucleic acid synthesis, metabolism, and stress tolerance (Thompson et al 2011 , Kelly et al 2013 , Enav et al 2014 ). Soil environments are also important reservoirs for viruses that encode AMGs (Sun et al 2023a ). Phages can also provide their host bacteria beneficial traits through lysogenic conversion where they integrate into bacterial chromosome as prophages.…”
Section: Introductionmentioning
confidence: 99%